Organizational and economic principles of financial monitoring of national business entities in the context of national security - Poliova, Nataliya; Polova, Lesya; Stepanenko, Sergey; Izmailov, Yaroslav; Varenyk, Volodymyr; Akimov, Oleksandr (Edelweiss Applied Science and Technology, 2024)
The article considers the overall landscape and peculiarities of national regulations in the field of financial monitoring, in the retrospect and in the current moment. In particular, the cases of EU as a whole, the Netherlands, the USA, New Zealand and Australia are considered, through the prism of the necessity of compliance with FATF requirements and increased national security threats.